Inequality, Redistribution and Wage Progression. (4th May 2022) - Blundell, Richard
Abstract : Changes in the structure of work and families over the last four decades have increased many labour market inequalities. Growing earnings inequality, adverse labour market 'shocks' for the low‐educated, and geographically concentrated pockets of deprivation are among the most evident of these in Britain. The decade since the financial crisis has brought these inequalities into sharper focus, and the Covid‐19 pandemic has further exacerbated labour market inequality. The object of this paper is to highlight the key role played by poor wage progression for lower‐ and middle‐educated workers in understanding inequality in the labour market and for designing effective policy responses. It is unlikely that we can address all the concerns about low wages, wage progression and earnings inequality through the tax and welfare system alone. The challenge is how best to balance tax and welfare benefit policy with other policies, such as human capital policies, the minimum wage and labour market regulation. The results point to a mix of policies that aim to enhance wage progression for the lower‐educated within a welfare system that supports low‐earning families and provides a minimum wage floor for hourly wages.